Supportive Educative Interventions Based on The Information Motivation Behavioral Skills on the Compliance of Antiretroviral Therapy and Quality of Life in HIV Patients - Nursalam, Nursalam; Martawinarti, Rts Netisa; Wahyudi, Andri Setiya (International Journal of Psychosocial Rehabilitation, 2020)
Anthroviral therapy (ART) is the only drug to treat the HIV virus. Non-adherence to ART is a major factor in treatment failure and one of the causes of decreased quality of life in HIV patients. This Study aimed was to improve the compliance and quality of life in patients with HIV. A quantitative research with quasi-experimental design with 30 control samples and 30 intervention samples, the sampling technique used was purposive sampling, the dependent variable was adherence and quality of life. In this study using instruments in the form of a questionnaire consisting of 3 behavioral skills, compliance (MARS), and quality of life (WHOQOL). Analysis using Shapiro Wilk, paired T test and Wilcoxon sign rank test. Interventions are given 3 times a month. The results showed the effect of intervention on adherence seen from the p value of 0.014 (<0.05), while for behavioral skills and quality of life of the control and intervention groups both had an influence, but the delta value of the intervention group had a significant difference in value of quality of life, while behavioral skills do not have meaningful value differences. Improving adherence and quality of life in HIV patients is very dependent on the behavioral skills possessed by HIV patients, which are closely related to the information and motivation possessed. Techniques for providing information, self- motivation and social support are carried out using supportive educative methods, namely providing education through learning methods, guidance and support.